INVENTORY PLANNING AND OPERATIONAL PERFORMANCE OF HOTELS IN PORT HARCOURT (World Bulletin of Management and Law, 2024)
This paper assessed the impact of inventory planning on operational performance of Hotels in Port Harcourt. Specifically the study examined how inventory planning impacts timely service delivery, cost reduction and waste minimisation. The study was conducted on fifty-five (55) hotels within Port Harcourt which were selected using cluster sampling techniques. The sample size was 385; hence, seven copies of the research instrument were administered to each of the hotels purposefully. The study adopted a descriptive survey design and data was gathered via the use of 5-point Likert scale questionnaire. The validity and reliability of the survey instrument were guaranteed by conducting confirmatory factor analysis which comprised the assessment of discriminant validity, convergent validity, composite reliability and Average Variance Extracted. The hypotheses were analysed using Partial Least Square structural equation modelling (PLX-SEM). The result showed that inventory planning possesses a significant positive impact on operational performance of hotels in Port Harcourt showing that it could influence timely service delivery, cost reduction and waste minimisation to the tune of 84.8%, 87.8% and 82.4% respectively. Based on these results, it was concluded that inventory planning is a good predictor of operational performance of Port Harcourt hotels. Consequently, the study advised hotel management to embrace the integration of AI, data analytics and modern innovative technology that could predict future inventory requirement by analysing the historic data on previous inventory usage. This would encourage a proactive rather than reactive response to inventory needs thereby preventing unnecessary halt in daily operation and delay in service delivery. By so doing they would also have enough time to bargain fair prices with suppliers; thereby contributing to cost reduction